A Complete Review of Cobalt-based Electrocatalysts Applying to Metal-Air Batteries and Intermediate-Low Temperature Solid Oxide Fuel Cells - Zhou, W.; Wang, X.; Zhu, Y.; Dai, J.; Zhu, Y.; Shao, Zongping (2018)
© 2018, Materials Review Magazine. All right reserved. The over-exploitation and over-utilization of fossil fuel resources such as petroleum and coal has aggravated energy and environment problem in the 21st century, and urged the development of highly-efficient and cost-effective energy conversion and storage devices to become the research topic of this new era. Among many candidates of energy conversion and storage devices, metal-air batteries and intermediate-low temperature solid oxide fuel cells can efficiently convert chemical energy into electric energy, and enjoy the advantages of low cost, high efficiency and environmental friendliness. Hence, they have provoked intensive and fruitful research endeavors with amazing achievements over the past decade. However, the sluggish kinetics of the oxygen reduction and evolution reactions greatly reduces the energy conversion efficiency, and consequently increases the application cost and severely hinders the commercialization of these two devices. Cobalt-based electrocatalysts, as highly efficient cathode materials with lower cost than noble metals, feature mixed ionic and electronic conductivity which can effectively reduce polarization and contribute to high catalytic activity for oxygen reduction and evolution reactions, and thereby have been holding growing interest recently. For metal-air batteries, cobalt-based electrocatalysts such as simple oxides, spinel oxides, perovskite oxides, and others can significantly improve the discharge capacity and cycle life, and simultaneously, lower the charge voltage and polarization. On the other hand, the catalytic activity and stability need to be further enhanced, and the catalytic mechanisms and active sites deserve further rational exploration and ascertainment. Similarly, cobalt-based electrocatalysts including La1-xSrxCoO3-d, La1-xSrxCo1-yFeyO3-d, Ba1-xSrxCoyFe1-yO3-dand cobalt-based double perovskites show evident efficacy in reducing the cathode polarization resistance and area specific resistance as well as increasing the power density, while nonetheless sustaining a generally higher thermal expansion coefficient and a rather poor stability compared to some other competitors. To further improve the catalytic performance of cobalt-based electrocatalysts for metal-air batteries and intermediate-low tempe-rature solid oxide fuel cells, researchers have developed many useful and productive methods, exemplified by metal elements doping, composite cathode materials preparation, and noble metals decoration. This review provides a brief introduction of the structure and working principle of metal-air batteries and intermediate-low temperature solid oxide fuel cells, and a vivid description upon the latest attempts and achievements for the fabrication, modification and performance of the rich variety of cobalt-based electrocatalysts, mainly including simple oxides, perovskites oxides, spinel oxides and double perovskites.